Heterophil to lymphocyte ratio and tonic immobility reactions to preslaughter handling in broiler chickens treated with ascorbic acid - Zulkifli, I.; M.T., Che Norma; Chong, C.H.; Loh, T.C. (Elsevier, 2000)
Stress and fear responses were evaluated in broiler chicks that were pretreated for 24 h with 0 ppm (control) or 1,200 ppm of L-ascorbic acid (AA) in their drinking water. The birds were subsequently subjected to either upright handling (UH) or inverted (IH) handling for about 45 s. Heterophil (H) counts, lymphocyte (L) counts, and H/L ratios (H/L) ratios were determined immediately (T0) and at 20 h (T20) following the handling treatment. The H/L ratios were similar for both groups at T0, whereas 20 h after the handling treatment, AA-supplemented birds had lower ratios than controls, resulting in a significant water treatment × time of blood sampling interaction. Inverted handling had negligible effect on H/L ratios but augmented tonic immobility (TI) durations as compared with UH. Irrespective of handling procedure, supplemental AA reduced underlying fearfulness, as measured by TI reaction. Neither water treatment nor handling method had significant effect on number of attempts to induce TI.